KINERJA PENYULUH PERTANIAN DALAM PENYUSUNAN PROGRAMA PENYULUHAN PERTANIAN DI KECAMATAN ANDOOLO KABUPATEN KONAWE SELATAN - Mardin, Mardin (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2025)
The efficacy of agricultural extension programs in the Andoolo Subdistrict remains constrained by numerous challenges, including suboptimal program planning that does not adequately align with farmers' needs and regional potential. This suboptimal planning is attributable to limited competencies, the dynamics of extension tasks, and the phenomenon of extension workers changing professions. Consequently, the effectiveness of agricultural extension implementation at the field level is also diminished. The objective of this study is to ascertain the extent of the performance of agricultural extension workers in the development of programs in Andoolo Subdistrict, South Konawe Regency. The present study employs a qualitative approach, utilizing a descriptive research design. The selection of informants was deliberate. The objective of this study is to assess the performance level of agricultural extension workers in the development of agricultural extension programs. The analysis was conducted in a descriptive manner, employing a combination of qualitative and quantitative methodologies. The findings indicate that the performance of agricultural extension workers in developing agricultural extension programs in Andoolo Subdistrict, South Konawe Regency, is satisfactory, with an average NPK score of 88.08. Extension workers have been able to carry out most of the stages of program development systematically, particularly in the stages of program refinement and approval, which reached the very good category. Nonetheless, there is still room for improvement in the stages of determining activity plans and planning monitoring and evaluation methods. These methods should be more closely aligned with the objectives and problems faced by farmers.